Secondhand Smoke as an Indirect Cause of Stunting: A Study at Nipah Health Center in North Lombok - Wardani, Yuniar; Nugraheni, Irin Azzahra; Hariyanti, Baiq Qatrunnada (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Stunting is a growth and development disorder in children resulting from poor nutrition, repeated infections, and inadequate psychosocial stimulation. Children affected by stunting are more vulnerable to various diseases. Long-term consequences include impaired cognitive and motor development, along with increased healthcare costs. Exposure to secondhand smoke, whether direct or indirect, is believed to contribute to stunting. This study aimed to investigate secondhand smoke exposure as an indirect cause of stunting.Method: This study used a cross-sectional approach with a sample of 99 children under five years old residing in the Nipah Health Center area, Malaka Village, North Lombok. The sample was taken using stratified proportional random sampling. Descriptive statistics and Chi-square tests were employed to analyze the data and test the research hypothesis.Result The prevalence of stunting was 38.38%. Although none of the mothers reported smoking during pregnancy, 98.98% of them were exposed to cigarette smoke from their husbands, family members, or neighbors. Exposure occurred multiple times in both home and public environments, typically lasting less than 15 minutes. The statistical analysis showed no significant association between secondhand smoke exposure and stunting. Despite the lack of a statistically significant relationship, exposure to secondhand smoke remains a public health concern. Preventive measures should be prioritized. Health promoters are encouraged to intensify anti-smoking campaigns. Smoking cessation counseling should be delivered door-to-door, particularly targeting households with pregnant women and toddlers. Educational materials such as flyers, short messages, and inspirational stories disseminated via social media platforms like WhatsApp can serve as effective health promotion tools.